Eficácia dos antiparasitários utilizados no controle parasitário de equinos provenientes de estabelecimentos militares do estado do RS - Flores, Alexandra Geyer (2019)
Parasitism has a prominent place when it comes to horse health, due to the consequent damages caused by gastrointestinal parasites. The treatment of infections caused by nematodes is based on the use of antiparasitics. However, the indiscriminate and inappropriate use of these drugs has led to signs of parasitic resistance to anthelmintics. The objective of this study was to evaluate the efficacy of the main classes of antiparasitic agents (ATP) including: benzimidazoles (febendazol), pyrimidines (pirantel pamoate), macrocyclic lactones (ivermectin and moxidectin), as well as the combination of two active principles, ivermectin and pirantel pamoate, used in parasitic control in adult and young horses from military environments. The study was carried out in military properties, located in the municipalities of Itaara and São Borja, RS, from January to December 2018. The intervals between the treatments of the animals were performed from 4 weeks to 90 days and the rotation of the active principles of the antihelminths was done at each treatment. Coproparasitological evaluations were determined by the fecal egg count reduction (R-OPG) test, and the determination of prevalent helminth genera and species in establishments. The results obtained demonstrated the parasitic resistance of cystostomines to febendazole, moxidectin in young animals, to pirantel pamoate in adult animals. However, ivermectin was inconclusive for young horses and moxidectin in adult animals. The detection of the anthelmintic resistance found in the studied population demonstrated the need to establish adequate parasitic control in order to reduce unnecessary costs, delaying the development of ATP resistance, and reducing losses caused by parasites.